Adenosine Triphosphate‐Competitive mTOR Inhibitors: A New Class of Immunosuppressive Agents That Inhibit Allograft Rejection. Issue 9 (4th August 2014) - Rosborough, B. R.; Raïch‐Regué, D.; Liu, Q.; Venkataramanan, R.; Turnquist, H. R.; Thomson, A. W.
<x xml:space="preserve">Abstract</x> The mechanistic/mammalian target of rapamycin (mTOR) is inhibited clinically to suppress T cell function and prevent allograft rejection. mTOR is the kinase subunit of two mTOR‐containing complexes, mTOR complex (mTORC) 1 and 2. Although mTORC1 is inhibited by the macrolide immunosuppressant rapamycin (RAPA), its efficacy may be limited by its inability to block mTORC1 completely and its limited effect on mTORC2. Adenosine triphosphate (ATP)‐competitive mTOR inhibitors are an emerging class of mTOR inhibitors that compete with ATP at the mTOR active site and inhibit any mTOR‐containing complex. Since this class of compounds has not been investigated for their immunosuppressive potential, our goal was to determine the influence of a prototypic ATP‐competitive mTOR inhibitor on allograft survival. AZD8055 proved to be a potent suppressor of T cell proliferation. Moreover, a short, 10‐day course of the agent successfully prolonged murine MHC‐mismatched, vascularized heart transplant survival. This therapeutic effect was associated with increased graft‐infiltrating regulatory T cells and reduced CD4+ and CD8+ T cell interferon‐γ production. These studies establish for the first time, that ATP‐competitive mTOR inhibition can prolong organ allograft survival and warrant further investigation of this next generation mTOR inhibitors.